World cinema and the visual arts - Gallagher, David (Anthem Press, 2012)
World Cinema and the Visual Arts combines new analyses of two subjects of ongoing research in the field of humanities: cinema and the visual arts. The films analysed encompass a wide geographical base, and have been drawn from a diverse array of cultural traditions
Title from publisher's bibliographic system (viewed on 02 Oct 2015)
Keywords: Film; Kunst; Ästhetik; Motion pictures / Aesthetics; Art; Konferenzschrift -- 2010 -- New Orleans, La.